Kajian Krimonologis Penanganan Kejahatan Percabulan Terhadap Anak - Rafli Rizki Rasyid; Deassy Jacomina Anthoneta Hehanussa; Hadibah Zachra Wadjo (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: This article discusses cases of sexual immorality against children which continue to increase from time to time in terms of quantity and quality. The perpetrators of sexual abuse against children are mostly from the environment around which the child is locatedPurposes of the Research: This article aims to examine and discuss the factors causing the crime of child sexual abuse and the obstacles encountered by the West Seram Police. Methods of the Research: The research method used in this research is the juridical-empis method or in other words the sociological legal research method and is called field research. This type of research is analytical using a juridical-empirical approach. The data used include primary data, namely direct data and secondary data, namely indirect data.Results of the Research: The results of this study indicate that the incidence of fornication against children in the West Seram District Police increased due to alcohol, economic factors, lack of parental supervision and mass media factors. And the obstacles encountered were the lack of legal understanding from the community so that they were less cooperative in fulfilling the summons of investigators.